Trends in Ambient Intelligent Systems The Role of Computational Intelligence - Ravulakollu, Kiran Kumar; Khan, Mohammad Ayoub; Abraham, Ajith; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book demonstrates the success of Ambient Intelligence in providing possible solutions for the daily needs of humans. The book addresses implications of ambient intelligence in areas of domestic living, elderly care, robotics, communication, philosophy and others. The objective of this edited volume is to show that Ambient Intelligence is a boon to humanity with conceptual, philosophical, methodical and applicative understanding. The book also aims to schematically demonstrate developments in the direction of augmented sensors, embedded systems and behavioral intelligence towards Ambient Intelligent Networks or Smart Living Technology. It contains chapters in the field of Ambient Intelligent Networks, which received highly positive feedbackduring the review process. The book contains research work, with in-depth state of the art from augmented sensors, embedded technology and artificial intelligence along with cutting-edge research and development of technologies and applications of Ambient Intelligent Networks. This book is intended to introduce ideas, methods, technologies of the future development of humanity, Science and Technology.
Neurocognitive Robot Assistant for Robust Fall Detection .-Smart Robot Control via Novel Computational Intelligence Methods for Ambient Assisted Living -- Valorization of Assistive Technologies for Cognition: Lessons & Practices -- Safe and Automatic Addition of Fault Tolerance for Smart Homes Dedicated to People with Disabilities -- Smart Homes in the Era of Big Data -- An Investigation of The Use of Innovative Biology-based Computational Intelligence in Ubiquitous Robotics Systems: Data Mining Perspective -- Ambient Stupidity -- Security Implementations in Smart Sensor Networks -- Automatic Music Composition from a Self- Learning Algorithm.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence